1982
DOI: 10.1093/ajcn/35.2.319
|View full text |Cite
|
Sign up to set email alerts
|

A survey of the anemia status of preschool age children and pregnant and lactating women in Jamaica

Abstract: An island-wide anemia survey was conducted in Jamaica on pregnant and lactating women and preschool age children. The results indicate that anemia is a serious public health problem in Jamaica. Of pregnant women, 61.6% had Hb levels below 11.0 g/dl. Of lactating women 58.7% had Hb levels below 12.0 g/dl. Of preschool age children 69.1% had Hb levels below 11.0 g/dl. Public health and fortification programs for the control of anemia have been implemented by the government and are currently being reviewed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
1
1

Year Published

1983
1983
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 4 publications
0
3
1
1
Order By: Relevance
“…standard) can not be attributed to pregnancy because their non-pregnant and apparently healthy counterparts had similar hemoglobin level (10.0 ± 0.75/100 ml). A physiological fall in hemoglobin level as reported in the literature (Simmons et al 1982) was not observed in this study. The prevalence of anemia was similar when the results of present study were compared with those of a nation-wide nutrition survey (Government of Pakistan, 1970).…”
Section: Hemoglobincontrasting
confidence: 51%
“…standard) can not be attributed to pregnancy because their non-pregnant and apparently healthy counterparts had similar hemoglobin level (10.0 ± 0.75/100 ml). A physiological fall in hemoglobin level as reported in the literature (Simmons et al 1982) was not observed in this study. The prevalence of anemia was similar when the results of present study were compared with those of a nation-wide nutrition survey (Government of Pakistan, 1970).…”
Section: Hemoglobincontrasting
confidence: 51%
“…The present study reported a high frequency of anaemia (44%) in women attending labour. This figure is some what comparable to those reported in Bahrain (50%) 11 and Kuwait (39.7%) 10 , and lower than the figures reported in Jordan (56.7%) 12 , Ghana (54%) 13 , India (over 70%) 14 , Liberia (78%) 15 , Guyana (73.9%) 16 , and Jamaica (61.0%) 17 . On the other hand, this figure is distinctly higher than the reported ones in: Egypt (22.1%) 18 and Northern Ireland (19.8%) 19 .…”
Section: Discussionmentioning
confidence: 38%
“…In addition, a large proportion of the population in all age groups suffer from varying degrees of anaemia, which available evidence suggests is caused primarily by a deficiency of iron. Deficiencies in folate and vitamin B 12 have been noted occasionally in Trinidad and Tobago and Guyana among nationals of East Indian origin, but their prevalence is much less than that of iron deficiency [2][3][4][5][6][7][8][9][10][11][12][13].…”
Section: Discussionmentioning
confidence: 99%